Pengaruh Perceived Ease of Use, Perceived Enjoyment, Perceived Usefulness, dan Satisfaction terhadap Continued IT Usage Intention: Expected-Confirmation Model (ECM) - Putra, Erlangga Dwi; Athaullah, Salsabilla; Yusuf, Abdul (Jurnal Maksipreneur, 2023)
Fundraising activities digitally for various projects are growing in Indonesia, especially after the Covid-19 Pandemic appeared. The psychographics of the Indonesian people who are friendly have made them voluntarily donate to humanitarian activities. Kitabisa.com is one of the most popular crowdfunding platforms in Indonesia for online fundraising. The study’s purpose is to determine the Perceived Ease of Use, Perceived Enjoyment, Perceived Usefulness, and Satisfaction effect on Continued IT Usage Intention on the Kitabisa.com platform. 50 users of the Kitabisa.com platform were used to be a sample and taken using the saturation sampling technique or saturated sampling because of the suitability of the research characteristics. To analyze data, researchers conducted a path analysis using the Statistical Package for the Social Sciences (SPSS). Based on the study results, Perceived Ease of Use and Perceived Enjoyment significantly and directly affect satisfaction. In addition, satisfaction significantly influences the Continued IT Usage Intention. Meanwhile, only Perceived Usefulness significantly and indirectly affects the Continued IT Usage Intention through satisfaction. Furthermore, researchers also found that Perceived Ease of Use, Perceived Enjoyment, Perceived Usefulness, and Satisfaction were confirmed able to meet the expectations of users through the confirmation variable.